Textbooks Equipped with Augmented Reality Technology for Physics Topic in High-School - Fauzi Bakri; Oktaviani Marsal; Dewi Muliyati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
This article aims to publish research results on the development of physics textbooks equipped with 3D media based on Augmented Reality technology. AR Technology can provide solutions when students face difficulties illustrating physics material in physics learning textbooks. This research uses the research & development method of the Dick & Carey model. The resulting book displays physics material in multi representations with verbal forms, pictures, tables, graphs, mathematical equations, and 3D media. Augmented Reality technology-based multi representation is displayed with a marker that is scanned through a smartphone application with an Android system. The scanning process requires an average of two seconds from each marker. The time of this scan shows that the media produced is more effective and efficient when compared with the activities of searching and downloading animations or videos by students. The feasibility of the book was tested with a Likert scale questionnaire instrument. For material, the worthiness was 71.45% while 93.3% for the media. The trial results are limited to five materials giving N-Gain values ranging from 0.3 to 0.47. Based on these results it can be concluded that the book model enriched with 3D media with AR technology is already feasible as a textbook in learning physics.